A Progression of Discourse in the Science Classroom - Wiesen, Jennifer (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
The framework of the NGSS requires the development of skills central to the field of science. Scientific discourse is necessary for developing these skills, but the use of discourse is absent from many science classrooms. Possible reasons for this could be that teachers do not know how to incorporate methods into their classroom. This manuscript addresses methods that can be used to develop the discursive skills necessary for students to participate in activities central to science. Methods are described in a progression from introductory vocabulary use and explanation of ideas, discussion skills, and finally, the integration of skills to perform complex tasks such as inquiry and argumentation.